Pembentukan Harmoni Sosial Melalui Implementasi Moderasi Beragama - Fathurrohman, Fathurrohman (Proceedings of Annual Conference for Muslim Scholars, 2023)
This research aims to understand how important religious moderation is in the surrounding environment. The method used in this research is normative juridical or uses descriptive methods by collecting data sources based on previous research carried out through books, e-books, and journals. Religious moderation is crucial, especially in a multicultural environment like Indonesia. Religious moderation creates a harmonious, peaceful and hormonal religious life from the surrounding environment to the nation.